EFFECT OF DIETARY ASPIRIN ON SOME BLOOD BIOCHEMICAL PARAMETERS OF BROILERS REARED IN HIGH DENSITY - Shaker, Motthena Mahmoud (The Iraqi Journal of Veterinary Medicine, 2009)
The objective of this study was to determine the effect of adding aspirin to the diet on somebiochemical parameters such as blood serum glucose , cholesterol , uric acid , total protein ,phosphorus and calcium concentrations of broilers reared in high density (15 birds / m ) . A 90 chicks 7days old were distributed into two treatments (45 chicks per treatment ) , T1 chicks fed a diet withoutaspirin (control) , chicks in T2 fed a diet supplemented with 0.2 % aspirin (2 mg aspirin / kg feed) .Each treatment subdivided into three replicates and each replicate reared in 1 X 1 m pen . The dataobtained revealed the following:Blood serum glucose concentration were 189 mg /100 ml , cholesterol concentration were 207mg /100 ml , uric acid concentration were 4.6 mg /100 mll of T1 chicks at 7 weeks of age , adding 0.2% of aspirin to the diet (T2) decreased blood serum glucose , cholesterol and uric acid of broiler chicksto 178 , 182 and 4.2 mg /100 ml respectively , in the same time adding aspirin to the diet increasedsignificantly (P<0.01) total protein concentration which were 5.1 gm /100 ml compaired with 4.6gm/100 ml of control chicks (T1) at 7 weeks of age . Adding aspirin to the diet increased significantly(P<0.01) blood serum phosphorus and calcium concentrations which indicated the importance ofadding aspirin in broiler diet to rebalance blood biochemical parameters and reducing crowding stressduring high density production